Social media marketing and purchase decision: Insights from Indonesian MSMEs - Wana Pramudyawardana Kusuma Negara (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2024)
Purpose — This study aims to examine and analyze the effects of various social media marketing dimensions—entertainment, customization, interaction, and trendiness—on purchase decisions.Method — The study focuses on micro-, small-, and medium-sized enterprises (MSMEs) in Indonesia. Data were collected through an online survey of 245 consumers who actively use social media and follow at least one MSME social media account. Purposive sampling methods were used to select respondents. The data were analyzed and hypotheses tested using Structural Equation Modeling—Partial Least Squares (SEM-PLS).Result — The study confirmed that customization, interaction, and trendiness have a positive and significant effect on purchase decisions. Conversely, entertainment was found to have a non-significant effect. Among the variables, interaction had the greatest impact on driving purchase decisions.Novelty — This study focuses on micro-, small-, and medium-sized enterprises (MSMEs) in Indonesia within the context of social media marketing. MSMEs are increasingly recognizing the advantages of leveraging social media to promote their products and brands. Additionally, this research directly examines the impact of social media marketing on purchasing decisions among MSMEs in Indonesia.